Economics as a Science -or viewed from the perspective of scientists in other fields - Joaquim Vergés-Jaime (CADMUS, 2020)
The aim of this article is to underline that the core paradigm of mainstream economics, the economics' standard model (ESM), rests upon an explanatory theory that draws on deductive assumptions which are not supported by what observations of the reality of market economies shows us; either in the present day or historically. A theoretical setting that, therefore, fails to provide a proper explanation of how our economic system –a market economy based on private firms, or capitalist– operates in reality. Or that it does not explain it well for the vast majority of cases, goods, sectors or markets. All of which, moreover, I am far from being the first one to highlight. This `deficiency' of the ESM has relevant implications. It is something more than a pure theoretical issue. The fact that this explanatory model (much dominated by microeconomics) postulates that the `free-play market' leads spontaneously to an optimum of social utility (a general equilibrium of efficient markets) has nevertheless implications beyond the economic discipline. In the political arena neoliberalism draws on this theoretical postulate to defend its principles of no (or minimum) intervention by governments in the economy, of no (or minimum) regulation of markets; i. e., to defend what lies behind the well-known expression `the less State the better': minimum public expenditure, minimum taxes. And, furthermore, this general equilibrium model that supports such a postulate dominates the way economics is customarily taught, i.e., how the workings of a market economy is explained in textbooks and in university classrooms.
Keywords: A11; B41; D21; D22; 330; Economics' epistemology; Mainstream orthodox economics; Scientific method; Mainstream Economics' Assumptions